Image and likeness: social sciences in the face of the advent of artifcial intelligence - Leal, Alfredo (2024)
Times of crisis transform social scientists into particularly divided beings. Based on the knowledge they have been accumulating, they write about the probable worsening of the crisis, but they do so with the secret hope that it will not happen. They make proposals on the ways of solution that will least affect the quality of life of the vast majority of citizens, but they do so with the secret fear that they are not viable. In other words, either they want to be surprised by reality and are afraid of not being surprised, or they do not want to be surprised by reality and are afraid of being surprised.